Analisis Rasio Profitabilitas Sebagai Alat Ukur Kinerja Keuangan Perusahaan Asuransi Terdaftar di Ojk (Studi Pada PTb. Prudential Life Assurance Dan Pt. IAI Financial Periode 2015-2019) - I’tisoma Billah, Zahida; Aziza, Ummu (INAIFAS Press, 2021)
This study aims to determine the financial performance of PT Prudential Life Assurance and PT AIA Financial based on profitability ratio analysis in the 2015-2019 period. The research method uses descriptive quantitative research, descriptive quantitative research is a method that explains or analyzes a problem from a data based on the calculation of the numbers from the research results. where in this study describes the assessment of the financial performance of Islamic insurance companies using financial statements. The results showed that the financial performance of PT. Prudential Life Assurance for the period 2015-2019 based on Return On Assets (ROA) shows thecategory healthy with ratio values ​​of 34%, 24%, 8%, 7%, and 7%. while the results of the calculation of Return On Equity (ROE) show thecategory healthy with a ratio value of 48%, 32%, 30%, 33%, and 41%. Financial performance of PT. IAI Financial 2015-2019 period based on Return On Assets (ROA) indicates acategory healthy with a ratio value of 6%, 6%, 5%, 4% and 7%. Then the results of the calculation of Return On Equity (ROE) show thecategory healthy with a ratio value of 37%, 36%, 28%, 19%, 23%.